PENYIDIKAN TINDAK PIDANA ANCAMAN KEKERASAN MELALUI LAYANAN PESAN SINGKAT BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Elisabet Situmeang; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
One of the many electronic media used by the people in their daily activities namely mobile phones. The cell phone is a communication tool to make calls or send text messages commonly called SMS (Short Message Service). With the mobile phone making it easier for us to talk and send messages to other people without having to meet with the person. As for crimes arising out of the use of a cell phone that crime threats of violence via SMS. The perpetrator committed the act because the perpetrators feel confident that their crimes will be difficult to be traced or known by others and evidence can be easily removed so it can be hard to find. In the case of violent threats via SMS, investigators did not take action against the detention of the suspect, as stated in Article 21 paragraph 4 (a) Criminal Procedure Code.This type of research is classified in socio-juridical kind of research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Special Criminal Investigation Directorate Riau Police, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews, questionnaires and review of the literature.From the research, there are three main issues that can be inferred. First, the investigation of criminal acts of violent threats via SMS in the Special Criminal Investigation Directorate Riau Police did not run well because the perpetrator has not been found. Second, the obstacles faced in the investigation of criminal acts of violent threats via SMS in the Special Criminal Investigation Directorate Riau Police are suspects fled, infrastructure is inadequate, governance sequence complicated administration, the telkomsel who are not willing to be a witness and a limited the number of personnel investigator who has expertise in the communications technology field. Third, efforts made to overcome the obstacles the investigation of the crime of violent threats via SMS in the Special Criminal Investigation Directorate Riau Police are searching for suspects who fled, improve infrastructure to conduct investigations, following in accordance with the rules of procedure sequence administration, pointing Employees Civil Affairs Ministry of communication and Information of the Republic of Indonesia as an expert witness Telecommunications Informatics Electronics and add personnel investigator who has expertise in the communications technology field. Suggestions author, told investigators that immediately catch the perpetrators who flee and obstacles that occur during the implementation process of investigation can be overcome with efforts as much as possible to do.Keywords: Investigation - Threats of violence - Short Message Service